2015
DOI: 10.1016/j.scr.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A chemically defined substrate for the expansion and neuronal differentiation of human pluripotent stem cell-derived neural progenitor cells

Abstract: Due to the limitation of current pharmacological therapeutic strategies, stem cell therapies have emerged as a viable option for treating many incurable neurological disorders. Specifically, human pluripotent stem cell (hPSC)-derived neural progenitor cells (hNPCs), a multipotent cell population that is capable of near indefinite expansion and subsequent differentiation into the various cell types that comprise the central nervous system (CNS), could provide an unlimited source of cells for such cell-based the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Many matrix properties affect cellular response . Even small changes in substrate properties can lead to significant changes in cellular response .…”
Section: Discussionmentioning
confidence: 99%
“…Many matrix properties affect cellular response . Even small changes in substrate properties can lead to significant changes in cellular response .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the microarray platform was utilized to identify synthetic polymers that promote attachment, proliferation and self-renewal among human embryonic stem cell lines [33]. More recently, Brafman et al reported that this platform could be used to examine ECMs that regulate endodermal differentiation in human ESCs [35], as well as identify synthetic polymers that support neuronal differentiation of neural progenitor cells [41]. These aforementioned works primarily employed ECM microarrays to identify the ideal microenvironment niche for cell maintenance and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the microarray platform was used to select synthetic polymers that improve attachment, proliferation and self-renewal among multiple human ESCs lines over five passages 15 . More recently, it was reported that ECM microarrays were used to study the ECMs that regulate endodermal differentiation in human ESCs 16 , as well as identify synthetic polymers that promote neuronal differentiation of progenitor cells 17 .…”
Section: Introductionmentioning
confidence: 99%